No limite da razão: identificação e amor ao clube como gatilhos para o vício em apostas esportivas - Gundlach, Gabriela Noetzold (2025)
This study investigated whether fans with stronger identification and love for their club engage more in sports betting, considering emotional bonds as potential triggers for risky behaviors. The research was conducted with football fans from Rio Grande do Sul, Brazil, using a quantitative approach, descriptive design, and primary data collected through an online survey. The sample consisted of 400 respondents recruited through non-probabilistic snowball sampling. Validated psychometric scales were used to measure club identification, brand love, and betting involvement, in a five-point Likert format. The reliability of the instruments was assessed using Cronbach’s alpha, which yielded satisfactory values. Analyses included descriptive statistics, internal consistency assessment of the scales, and simple linear regression estimated by Ordinary Least Squares (OLS). The results indicated that club identification directly influences brand love and has positive effects on betting frequency and addiction. Brand love was also a significant predictor of these behaviors, suggesting that intense affective bonds may trigger risky practices. Betting addiction was found to be a determinant of betting frequency among fans. These findings highlight the importance of emotional dimensions in understanding sports consumer behavior, particularly in activities with psychological and financial impacts. From a practical perspective, the results contribute to ethical reflections on the role of clubs, agencies, and platforms in fostering harmful behaviors, reinforcing the need for regulations that prioritize mental health and protect vulnerable audiences. Finally, limitations related to the sampling method and the exclusive use of self-report scales are acknowledged, and future research is recommended to include qualitative methods and expand the sample to other regions and social profiles.